2014
DOI: 10.1007/s12529-014-9409-3
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Physical Activity and Risk Factors Among Taiwanese Older Adults

Abstract: There is heterogeneity among the trajectory patterns of physical activity across time in the older adults. Different strategies of physical activity promotion for the older people should be developed by the group characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 23 publications
4
34
1
Order By: Relevance
“…In this study, four physical activity trajectories (“inactive”, “decreasing”, “increasing”, and “stable active”) were identified among a sample of adults of Turkish descent, living in Berlin. Similar results were reported by Pan et al who described the same PA trajectories in a Taiwanese sample [ 26 ]. Similar trajectories (always sedentary, fast declining, stable moderate, and always active) were reported in a study from the U.S. among a sample of older women aged 70–79 years, however, the authors found no increasing trajectory which was explained with the high age of the study participants [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, four physical activity trajectories (“inactive”, “decreasing”, “increasing”, and “stable active”) were identified among a sample of adults of Turkish descent, living in Berlin. Similar results were reported by Pan et al who described the same PA trajectories in a Taiwanese sample [ 26 ]. Similar trajectories (always sedentary, fast declining, stable moderate, and always active) were reported in a study from the U.S. among a sample of older women aged 70–79 years, however, the authors found no increasing trajectory which was explained with the high age of the study participants [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar trajectories (always sedentary, fast declining, stable moderate, and always active) were reported in a study from the U.S. among a sample of older women aged 70–79 years, however, the authors found no increasing trajectory which was explained with the high age of the study participants [ 41 ]. Most studies describe three to four trajectories or patterns [ 19 , 26 , 41 ], and less often more are reported, as in a European study conducted in Spain with more than 1600 participants, reporting very diversified patterns (high PA—consistent, moderate PA—mildly decreasing, low PA—increasing, moderate PA—consistent, and low PA—decreasing) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Ku et al 9 draw data from four national surveys comprising 29 226 people and revealed that 86.0% of Taiwanese adults did not meet the national recommendations (at least 90 min/week spent in exercise/sports). Pan et al 10 reported that, among 4018 Taiwanese older adults, 47.8% of the respondents had a high probability of being physically inactive (<90 min/week). Elsewhere in mainland China, Lee et al 11 conducted a study focused on 61 582 urban men in Shanghai and found that 10.7% did not engage in regular exercise/sports (at least once a week for at least 3 months).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PA declines throughout 57 adolescence, into adulthood, and during the transition toward older age (2,5). While leisure time 58 physical activity (LTPA) patterns over time have been well described (6)(7)(8), a very limited 59 number of studies has examined variations in other PA domains, such as commuting (CPA), 60 occupational (OPA), and household (HPA) (9) and this after the age of retirement (10). Given 61 determinants of PA are domain-specific (11) and susceptible to change over the life course (12), 62 decline in PA could take place at different critical periods for each domains.…”
mentioning
confidence: 99%